Common Vetch, Valuable Germplasm for Resilient Agriculture: Genetic Characterization and Spanish Core Collection Development - De la Rosa, Lucía; López-Román, María Isabel; González, Juan M.; Zambrana, Encarnación; Marcos-Prado, Teresa; Ramírez-Parra, Elena (Frontiers in Plant Science, 2021)
Common vetch (Vicia sativa L.) is a legume used for animal feed due to its high protein content and great capacity for nitrogen fixation, making this crop relevant in sustainable agriculture. The Spanish vetch collection, conserved at the Spanish Plant Genetic Resources Center (CRF) is one of the largest collections of this species worldwide, including landraces, wild relatives mainly collected in Spain, and commercial cultivars, but also accessions of international origin. The analysis of the genetic diversity of this material, whose genome has not been sequenced yet, and the assembly of a representative collection could play a pivotal role in conserving and exploiting these genetic resources in breeding programs mainly in those focused on consequences and demands of climate change. In this work, a set of 14 Simple Sequence Repeat (SSR) reference alleles has been developed, and validated for genotyping over 545 CRF common vetch accessions from all over the world. All the tested markers were polymorphic for the analyzed accessions. At least 86 different loci were identified with 2 to 11 alleles per locus with an average of 6.1 alleles per locus. Additional analysis indicates that most of these SSR markers are transferable across closely related species of Vicia genus. Analysis of molecular variance (AMOVA) revealed that wild relatives have a higher genetic diversity than landraces. However, cultivars have similar diversity than landraces, indicating that genetic variability has been barely lost due to the breeding process. Low differences of genetic variations between Spanish and non-Spanish accessions have been observed, suggesting a high degree of diversity within Spanish genotypes, which provide 95% of the total genetic variation, so we have focused on characterizing these genotypes. Based on SSR, seed protein profiles and agro-morphological and passport data, a vetch core collection (VCC) containing 47 V. sativa accessions of Spanish origin has been established. In this collection, the characterization has been expanded using ISSR and new agro-morphological data, including drought tolerance characters. This VCC presents a minimum loss of genetic diversity and constitutes an invaluable material that can be used in future breeding programs for direct use in a resilient agricultural system.